X-ray-induced photo-chemistry and X-ray absorption spectroscopy of biological samples - George, G.; Pickering, I.; Jake Pushie, M.; Nienaber, K.; Hackett, Mark; Ascone, I.; Hedman, B.; Hodgson, K.; Aitken, J.; Levina, A.; Glover, C.; Lay, P. (Blackwell Publishing, 2012)
As synchrotron light sources and optics deliver greater photon flux on samples, X-ray-induced photo-chemistry is increasingly encountered in X-ray absorption spectroscopy (XAS) experiments. The resulting problems are particularly pronounced for biological XAS experiments. This is because biological samples are very often quite dilute and therefore require signal averaging to achieve adequate signal-to-noise ratios, with correspondingly greater exposures to the X-ray beam. This paper reviews the origins of photo-reduction and photo-oxidation, the impact that they can have on active site structure, and the methods that can be used to provide relief from X-ray-induced photo-chemical artifacts. © 2012 International Union of Crystallography Printed in Singapore-all rights reserved.